PERLIDUNGAN JUSTICE COLLABORATOR TINDAK PIDANA KORUPSI - Jupri Jupri (JURNAL AKTA YUDISIA, 2020)
ABSTRACT                The guaranted of protection to a Justice Collaborator is stipulated in Article 32 of the United Nations Convention Against Corruption, 2003) as ratified as Law Number 7 Year 2006 stipulates that each State Party is obliged to provide physical and psychological protection against witnesses and experts in the disclosure of criminal acts of corruption. As the development progresses of corruption disclosure in Indonesia, the arrangement of Justice Collaborator is then started to be regulated explicitly in Law Number 31 Year 2014 on Protection of Witness and Victim.               Although physical, legal and special protection guarantees against the Justice Collaborator already exist. In fact, in the disclosure of a crime of corruption committed crime, a witness of the perpetrator who cooperates with law enforcement gets bullied until threats are killed. For example in the disclosure of corruption cases involving a number of politicians Political Parties in Indonesia. Keywords: Justice Collaborator, Protection, Corruption